Analysis Of Ethnoscience Integrated Chemistry E-Modules On Reaction Rate Material To Strengthen Chemical Literacy Of High School Students - Rina Nugraheni; Heru Pratomo (Indonesian Journal of Chemical Education, 2024)
The fading national identity has led to the need for ethnoscience-based learning. Chemistry is one of the subjects in high school. One of the materials that is considered difficult for students is the reaction rate. The same learning media makes learning uninteresting and boring. This study aims to explore the needs of teachers and students for the development of teaching materials in the form of e-modules integrated with ethnoscience on the reaction rate material which is expected to strengthen students' chemical literacy. This research method is an exploratory survey. Data were obtained through interviews with teachers and semi-open questionnaires with students. The study was conducted on 5 teachers and 15 students from three different high schools in Yogyakarta City. The results of the analysis of grade XI students showed that 93.3% of students needed an ethnoscience-integrated chemistry module because it helped understanding, getting to know ethnoscience, was interesting, not boring, and made it easier, while teachers hoped that the reaction rate module developed was related to everyday life and interactive.